2022
DOI: 10.1186/s40795-022-00579-8
|View full text |Cite
|
Sign up to set email alerts
|

Beyond hemoglobin: uncovering iron deficiency and iron deficiency anemia using serum ferritin concentration among pregnant women in eastern Ethiopia: a community-based study

Abstract: Background Although the high burden of anemia among pregnant women in low-resource settings like Ethiopia is well documented, evidence is scarce on the underlying causes using biochemical tests. Therefore, this study assessed the iron status and factors associated with iron deficiency (ID) using serum ferritin concentration among pregnant women in Haramaya district, eastern Ethiopia. Methods A community-based cross-sectional study was conducted amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Three articles examined the association of meal skipping with maternal nutritional status. Two cross-sectional studies from Ethiopia showed that skipping meals during pregnancy was positively associated with under-nutrition (OR = 3.9, 95% CI: 1.09, 13.53) [ 22 ] and iron deficiency anemia [ 23 ] (RR = 1.29; 95% CI: 1.05, 1.57). The third cross-sectional study from Japan showed that healthy pregnant women who skipped breakfast two or more times per week ( n = 37) had lower intakes of protein after adjusting for energy intakes than those who did not skip breakfast ( n = 60) ( p = 0.019).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Three articles examined the association of meal skipping with maternal nutritional status. Two cross-sectional studies from Ethiopia showed that skipping meals during pregnancy was positively associated with under-nutrition (OR = 3.9, 95% CI: 1.09, 13.53) [ 22 ] and iron deficiency anemia [ 23 ] (RR = 1.29; 95% CI: 1.05, 1.57). The third cross-sectional study from Japan showed that healthy pregnant women who skipped breakfast two or more times per week ( n = 37) had lower intakes of protein after adjusting for energy intakes than those who did not skip breakfast ( n = 60) ( p = 0.019).…”
Section: Resultsmentioning
confidence: 99%
“…In summary, these results indicate that skipping meals during pregnancy may be related to maternal malnutrition [ 22 , 23 , 24 ], GDM [ 25 ], and weight status [ 26 ]. However, since most studies are cross-sectional in nature, it is unclear whether these associations are causal.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this regard, the burden is nearly 2–3 times higher in the regions of Tigray, Harari and Somalia as compared with the national estimate 64 96. This variation may be explained by the fact that 78% of women within the reproductive age group had low RBC folate concentrations and the concentrations become much lower among pregnant women 107 108. Additionally, ecologically, the burden is disproportionately concentrated in the highland sorghum khat mixed farming system 109.…”
Section: Discussionmentioning
confidence: 98%